A new species of Kuzinellus Wainstein, 1976 (Acari:Mesostigmata: Phytoseiidae) from Saudi Arabia, with a key to the world species. Issue 7 (3rd October 2017) - Kamran, Muhammad; Basahih, Jamal Saeed; Alatawi, Fahad Jaber
ABSTRACT: Kuzinellus bahaensis sp. nov . (Acari: Phytoseiidae) is described and illustrated from six female specimens collected from different host plants i.e. Ocimum basilicum L. (Lamiaceae), Conyza bonariensis (L.) (Asteraceae), Olea sp. (Oleaceae), Ziziphus sp. (Rhamnaceae), and grasses (Poaceae), from Tabuk and Baha provinces of Saudi Arabia. It is the first species representing the genus Kuzinellus Wainstein from Saudi Arabia. An identification key to the 50 world species of the genus Kuzinellus is provided. Illustrations of spermathecae of 43 Kuzinellus species are provided to show spermathecal variation among the species. http://zoobank.org/urn:lsid:zoobank.org:pub:65123214-91E4-4BCF-A57E-AB948F0BBE43